[LB.01.02] PHASE II RANDOMIZED SHAM-CONTROLLED STUDY OF RENAL DENERVATION FOR SUBJECTS WITH UNCONTROLLED HYPERTENSION – WAVE IV. (September 2017) - Schmieder, R.E.; Ott, C.; Toennes, S.; Gertner, M.; Dawood, O.; Saxena, M.; O'Brien, B.; Lobo, M.
Abstract : Objective: The aim of this double blind randomized sham-controlled study was to verify the blood pressure (BP) lowering efficacy of externally delivered focussed ultrasound for renal denervation (RDN). Design and method: The WAVE IV study was an international, randomized (1:1), sham-controlled, double blind prospective clinical study carried out in 13 institutions. Patients (18–80 years of age) had true treatment resistant hypertension with office BP > = 160 mmHg whilst taking 3 or more antihypertensive medications. The treatment consisted of bilateral RDN using therapeutic levels of ultrasound energy and the sham consisted of bilateral application of diagnostic levels of ultrasound energy. The primary objective was change in office BP and secondary objective change in 24-hour ambulatory BP at 24 week follow-up visit. Results: An interim analysis showing lack of evidence of antihypertensive efficacy by the externally delivered focused ultrasound in the RDN group over the sham group prompted termination of the trial. Out of 239 screened patients, 81 were treated. Neither changes in office BP at 24 weeks (sham: −18.9 ± 14 vs RDN: −13.2 ± 20 mmHg, p = 0.133), nor changes in 24-hour ambulatory BP at 24 week follow-up visit (sham: −5.90 ± 15 vs RDN: −7.11 ± 13 mmHg, p = 0.770) differed between the two groups significantly. Of note, no safety signal was observed. Medication changes were less than 15% throughout the first follow-up period of 24 weeks. In a subset urinary toxicological analysis disclosed full adherence in 77% at baseline and 82% at 6 months. Post hoc analysis revealed that stricter criteria for stabilisation of BP at baseline were associated with a numerically greater change in 24-hour ambulatory BP in the RDN group than in the sham group. Systolic BP changes were numerically greater in patients with pulse pressure < 65 compared to those with pulse pressure > = 65 mmHg. Conclusions: Our data did not prove that antihypertensive efficacy of the externally delivered focused ultrasound for RDN was greater than the sham effect. Post-hoc analysis suggested that the predominance of treatment resistant hypertensive patients with stiff arteries, and less stringent stabilisation of baseline BP may have hampered our trial.